Resolving issues in the genus Dioxys (Hymenoptera, Megachilidae, Dioxyini) in the West Palaearctic with a new identification key - T. J. Wood (ZooKeys)
The bee genus Dioxys is widely distributed across the Holarctic from the Mediterranean basin to western North America but is species-poor, and individual species can prove challenging to identify. Consequently, there has been a lack of consensus as to how many species actually exist. In the West Palaearctic, the number of species has varied from six to ten, depending on the worker. Due to a previously incorrect assessment of publication dates, Dioxys rotundatus Pérez, 1884, sp. resurr. is restored as the senior synonym of Dioxys moestus Costa, 1884, syn. nov. The relationship between this species and Dioxys atlanticus Saunders, 1904 is clarified, with the latter restricted to the islands of Gran Canaria and Tenerife (Spain). Dioxys rufipes Morawitz, 1875 is considered part of the West Palaearctic fauna, replacing “D. moestus” sensu Warncke (1977) in the eastern Mediterranean. Dioxys montanus Heinrich, 1977, sp. resurr. is revalidated from synonymy with Dioxys cinctus (Jurine, 1807). Dioxys pumilus Gerstäcker, 1869 is found to consist of four species, D. pumilus (eastern Mediterranean), Dioxys varipes De Stefani, 1887, sp. resurr. (western Mediterranean), Dioxys cypriacus Popov, 1944, sp. resurr. (Cyprus), and Dioxys hermonensis sp. nov. (Israel: Mount Hermon). A neotype is designated for D. varipes, and Dioxys falsificus Engel, 2023, syn. nov. is synonymised with it. This contribution produces a total of 13 species for the West Palaearctic region, and illustrates the degree to which persistent taxonomic problems exist even within small bee genera.